Rotational natural frequency indentification of a rotor-shaft system by using inertial measurement unit / Mazlyne Mat Akat - Mazlyne , Mat Akat (2018)
It is important to some plants and rotating machineries to identify the vibration characteristic of a structure to maintain their integrity. These rotating machinery/shaft while they are rotating has its own natural frequencies and mode shapes. Every rotating system have their own gyroscopic effect and this study is intended to use an inertial measurement unit directly to obtain system’s natural frequency. The objectives of this study is to determine the natural frequencies of a rigid rotor-shaft test rig setting in the lab which consist of 3 point at each respective disc and to perform animation of the mode shapes obtained from the inertial measurement unit reading. Literature review has been done to numerous journals or studies on the usage of the inertial measurement unit. Most of the studies or experimental setup using the inertial measurement unit to measure movement and navigation of a vehicle ,robotic movement and movement of human limbs. This research project involves the usage of few software such as VibraScout 6D, DASYLab 10, Measurement and instrumentation Explorer (MAX) and ME’scope VES 5 to acquire six degree of freedom data from inertial measurement unit, the impact hammer and tachometer data and for the purpose of data processing and animation. There are three experiment performed first the inertial measurement unit is placed at each three points of the three rigid discs while the motor runs accelerating from 0Hz to 50 Hz to find the natural frequencies. Second, the motor runs at specified natural frequency then again the inertial measurement unit is placed at those three points before the data obtained animated in ME’scope VES 5 to observe the mode shapes at each natural frequency. The third experiment involves the usage of impact hammer to excite the system and the data of the movement is then recorded by the IMU. There are 4 natural frequencies identified, that are 5.5Hz, 8Hz, 15Hz and 26Hz. The mode shapes at 5.5Hz and 15Hz being animated in this study for the purpose of testing the data applicability for animation. It is concluded that the inertial measurement unit data can be used to obtain natural frequencies and mode shapes in the form of rotating vibration. However, the validity and errors of data obtained is not investigated which can be done in other study in the future.